Kebiasaan Belajar dan Capaian Matematika Siswa: Bagaimana Korespondensinya? - Siti Nurhaliza; Fiki Alghadari; Neng Nurwiatin (S&Co Publishing, 2021)
Learning mathematics in depth has implications for the quality of achievement. However, students do not apply their best, or even the habit has not formed a consistent. This study aims to interpret how the correspondence between students' learning habits and their mathematics achievement. This observational research was conducted using the correlation technique. Data were obtained through questionnaires and tests from 30 students in one school in Karawang district. One subgroup is selected from a specified vocational school. The data distribution was analyzed, followed by analyzing the regression equation, and correlation analysis. Based on the results of data analysis, stated that the data is normally distributed, the regression is linear with a positive coefficient, and the correlation is significant. The results concluded that there was a relationship between learning habits and students' achievement. Research findings are also discussed. Changes in learning habits on mathematics achievement are estimated at 10%. This number can be said to be an indication of a relatively slow change. Therefore, if new pattern learning habits are implemented to students, for example through changes to the education curriculum, and with relatively slow approximated, then it is ideal when the impact on students' achievement is not yet very significant.